AN ANALYSIS OF THE MAIN CHARACTER THROUGH CHARACTERIZATION IN CINDERELLA 2021 MOVIE BY KAY CANNON - Made Wulan Lestari, Ida Ayu; Sri Rwa Jayantini, I Gusti Agung (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
The characterization analysis of the main character is given particular focus in this study. The data source in this study is the Cinderella 2021 movie written and directed by Kay Cannon. The main character in this Cinderella 2021 movie is a young girl named Cinderella, who is often called Ella, who has a dream to open a dress shop business. This study focuses more on the characterization of the main character in the Cinderella 2021 movie. The purpose of this study is to find out how the main character is described and interpreted based on the aspect of the character. The character aspects in question are divided into psychological, sociological, and physiological. Data were collected through observation. The method used in this study is a qualitative descriptive method. The data found in this study were 6 data, divided into 3 data on psychological aspects, 1 data on sociological, and 2 data on physiological aspects.